PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK PADA MATERI IPAS PERUBAHAN ENERGI SISWA KELAS IV SDN TAROKAN 3 KEDIRI - Cantika Sabrinatasari; Wahid Ibnu Zaman; Muhamad Basori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In fourth-grade science instruction at Tarokan 3 Elementary School, teachers do not use instructional media and still rely on teacher and student textbooks as teaching aids. This makes students less active in learning about energy transformations. Based on observations and interviews, only 15 of 40 students achieved the minimum grade point average (KKTP) (75). This study aims to determine the effectiveness of using the